2002
DOI: 10.1021/jp014099n
|View full text |Cite
|
Sign up to set email alerts
|

Positron Annihilation Studies in Silica Supported Nickel Carbonate Systems

Abstract: A number of silica supported nickel carbonate systems were studied by positron annihilation lifetime spectroscopy (PAS) and nitrogen gas adsorption method (BET) to evaluate the pore size distribution in the samples. Results show that the long-lived o-Ps component gives a pore size much smaller than the average pore radius obtained from BET analysis. This indicates that o-Ps represents the pores of smaller size in a sample with wide pore size distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Positron annihilation lifetime spectroscopy (PALS) has attracted interest due to its ability to dynamically probe open volumes, providing complementary insights into more widespread equilibrium techniques, such as gas sorption. This has been demonstrated for silica powders and films, ,, aluminosilicate gels, metal–organic frameworks, , zeolites, and layered materials. , The high sensitivity of PALS stems from the possibility of positrons binding with electrons in solids to form metastable ortho -positronium ( o -Ps) atoms, which are sufficiently long-lived to diffuse through open pore networks and be annihilated with a lifetime characteristic of the pore size . This property has recently been exploited in the characterization of zeolitic materials in discriminating the effectiveness of hierarchical pore networks in enhancing transport properties, in studying coking and detemplation mechanisms, , in assessing the micropore topology, , and in monitoring pore evolution during structural transformations …”
Section: Introductionmentioning
confidence: 99%
“…Positron annihilation lifetime spectroscopy (PALS) has attracted interest due to its ability to dynamically probe open volumes, providing complementary insights into more widespread equilibrium techniques, such as gas sorption. This has been demonstrated for silica powders and films, ,, aluminosilicate gels, metal–organic frameworks, , zeolites, and layered materials. , The high sensitivity of PALS stems from the possibility of positrons binding with electrons in solids to form metastable ortho -positronium ( o -Ps) atoms, which are sufficiently long-lived to diffuse through open pore networks and be annihilated with a lifetime characteristic of the pore size . This property has recently been exploited in the characterization of zeolitic materials in discriminating the effectiveness of hierarchical pore networks in enhancing transport properties, in studying coking and detemplation mechanisms, , in assessing the micropore topology, , and in monitoring pore evolution during structural transformations …”
Section: Introductionmentioning
confidence: 99%
“…The growing interest in the recent years in the positron annihilation studies on amorphous silica or silica gel material (not only bulk but also thin films) [1][2][3][4][5][6][7] revealed that positronium (Ps) formation occurs with high efficiency in intrinsic microvoids of molecular network which was confirmed with several experimental techniques like positron annihilation lifetime spectroscopy (PALS), 2 angular correlation of annihilation radiation (ACAR), 8 and age-momentum correlation spectroscopy (AMOC). 9 Now that to these events the stimulating and contemplated effect of coherent emission of γ-rays via Bose-Einstein condensation 10 has been added with a further motivation, which in fact beckons more intense investigations in the field.…”
Section: Introductionmentioning
confidence: 99%
“…[49][50][51] When the sample was slowly heated up to 420°C, the s 3 value suddenly fell by 0.175 ns and remained almost unchanged thereafter. However, the o-Ps intensity showed a small increase at 420°C and remained constant on the subsequent isothermal pyrolysis at 420°C for up to 45 min.…”
Section: Full Papermentioning
confidence: 99%